Disque denúncia como fonte de informações para análises criminais na Região Metropolitana de Salvador 2006-2011 - Portella, Daniel Deivson Alves (2013)
Introduction: Drug trafficking can be considered as one of the factors for the increase in homicides in large cities and metropolitan areas. The high frequency of crimes contributed to the population to make anonymous complaints about criminal acts through the Hotline program implemented in Bahia since 2005. Objectives: Analyze the Disk Denounce as a source of information for crime analysis in the Metropolitan Region of Salvador (MRS) from 2006 to 2011 and to assess the association between murder, drug trafficking and social indicators in Salvador in 2010. Methods: This was an ecological and descriptive study of multiple groups of explanatory type, taking the unit of analysis from the municipales of the MRS. It was used records of criminal complaints Disk Denounce, murders, people involved in drug trafficking registered by the Civil Police of Bahia and social indicators of the Brazilian Institute of Geography and Statistics (BIGS). Data were analyzed by calculating the absolute and relative frequency for complaints by class and type of subject. The Poisson regression model was used to investigate the association between the rate of murders (dependent variable), number of people involved in drug trafficking, the proportion of residents race / black (main independent variable) and social indicators (co variables). In the analysis we used the R statistical package software in the public domain. Results: Were registered in the period from 2006 to 2011, 65,575 complaints in RMS, distributed by the 13 municipalities of the RMS, drug trafficking was the most reported, representing a majority of all complaints in the class of narcotics complaints. In Salvador was registered 1,494 homicides in 2010, the murder rate of 70.4 per 100 thousand inhabitants. The multivariate analysis showed that there is a 10% increase in the proportion of people of race / black color in a neighborhood the average rate of murder increased 32.4%. This is an average increase of 17.4%, in neighborhoods that differ in 10 people involved in drug trafficking, both results showed a positive association with statistical significance. Final Considerations: The popular participation in reporting crimes and other offenses constitutes of an important aspect because primarily directs the actions of the police and cooperates with the State in fighting violence and secondly prevents the trivialization of violence.